The Internalization of Moral Values in Enhancing Students’ Awareness of Learning Facility Maintenance at MA Zainul Hafidz At-Taufiq Buwun Mas - Hamdi, Hamdi (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study is motivated by the limited empirical research examining the internalization of moral values (akhlaq) and students’ responsibility for maintaining learning facilities in Islamic secondary schools. It aims to identify models and strategies of moral value internalization and to analyze their impact on students’ awareness and maintenance behavior at MA Zainul Hafidz At-Taufiq Buwun Mas. The research employs a qualitative descriptive case study design, with data collected through in-depth interviews, observations, and documentation involving the head of the madrasah, Islamic education teachers, homeroom teachers, students, and supporting staff, and analyzed using Miles and Huberman’s interactive model of data reduction, data display, and conclusion drawing. The findings indicate that moral value internalization is implemented through three interrelated stages: value transformation, value transaction, and value transinternalization, with teacher role modeling and habituation practices emerging as dominant factors in fostering students’ moral awareness. These processes contribute to positive behavioral changes, reflected in increased student discipline, responsibility, and voluntary care for learning facilities, and are consistent with moral internalization theory and Social Learning Theory, which emphasize the importance of modeling and sustained practice. The study concludes that effective moral value internalization significantly enhances students’ awareness and responsibility toward maintaining learning facilities, thereby enriching the literature on moral and character education by linking moral internalization to environmental responsibility and providing practical guidance for strengthening value-based programs in madrasahs through consistent role modeling and participatory habituation. Future research is encouraged to extend this inquiry to broader institutional contexts and adopt longitudinal designs to capture long-term effects.